Current Antivirals and Novel Botanical Molecules Interfering With Herpes Simplex Virus Infection - Álvarez, Diana M.; Castillo, Estefanía; Duarte, Luisa F.; Arriagada, José; Corrales, Nicolás; Farías, Mónica A.; Henríquez, Adolfo; Agurto-Muñoz, Cristian; González, Pablo A. (Frontiers in Microbiology, 2020)
Herpes simplex viruses type 1 (HSV-1) and type 2 (HSV-2) are highly prevalent within the human population and are characterized by lifelong infections and sporadic recurrences due to latent neuron infection. Upon reactivations, HSVs may manifest either, symptomatically or asymptomatically and be shed onto others through mucosae body fluids. Although, HSVs can produce severe disease in humans, such as life-threatening encephalitis and blindness, the most common symptoms are skin and mucosal lesions in the oro-facial and the genital areas. Nucleoside analogues with antiviral activity can prevent severe HSV infection, yet they are not very effective for treating skin manifestations produced by these viruses, as they only reduce in a few days at most the duration of lesions. Additionally, HSV variants that are resistant to these antivirals may arise, especially in immunosuppressed individuals. Thus, new antivirals that can reduce the severity and duration of these cutaneous manifestations would certainly be welcome. Here, we review currently available anti-herpetic therapies, novel molecules being assessed in clinical trials and new botanical compounds reported in the last 20 years with antiviral activities against HSVs that might represent future treatments against these viruses.